Penyuluhan Resiko Jatuh Pada Lansia Di Masyarakat Pudak Payung - Widya Ervianta; Lilik Sigit Wibisono; Fitratun Najizah; Ni Kadek Krisna Dwi Patrisia; Lulu'ah Feby Purwanti (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2023)
The elderly are an age group that is prone to falls. The purpose of this service is to detect the risk of falls in the elderly and provide assistance in balance training as an effort to prevent the risk of falls in the elderly. Falls occur due to unintentional loss of balance resulting in failure of postural stability, or unexpected and sudden changes resulting in a position landing on the floor. Associated risk factors include current health status (living in the community, nursing home, hospital, frail or active state), diseases suffered (diabetes, hip fracture, stroke) and general changes related to aging (decreased balance, coordination, muscle strength, visual impairment, etc.). The output targets to be achieved are in the form of publications in accredited national journals and copyright for videos of community service activities. The method used is a fall risk detection examination using the Time Up and Go Test and continued with the provision of balance training, so that the elderly who have a risk of falling can be recognized as early as possible so that the provision of balance training can maintain and improve the balance of the elderly body.